ANALISA USAHA PENGARUH PEMBERIAN SILASE DAUN UBI KAYU TERHADAP PERTUMBUHAN TERNAK KAMBING PERANAKAN ETTAWA (PE) BETINA LEPAS SAPIH - Siswoyo, Purwo; Rusdhi, Alfath; Saputra, Agus Bayu (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The purpose of this study was to determine the rate of profit goat by feeding Cassava Leaf Silase, in the diet as a feed supplement. This research method using a completely randomized design (CRD) non factorial consisting of four treatments and five replications. This research was conducted Eksprimental and described with descriptive method. Treatment of feed given is as follows P1 80% Grass field + 20% Cassava Leaf Silase, P2 70% Grass Field + 30% Cassava Leaf Silase, P3 60% Grass Field + 40% Cassava Leaf Silase, P4 50% Grass Courses + 50% Cassava Leaf Silase. Parameter is the Cost of Production, Production (Revenue), Analysis of R / C Ratio and IOFC. These results indicate unreal effect on all research parameters of research include production costs, profit and loss analysis, R/C ratio and IOFC.